Management information systems concepts and applications - Rainer, R. Kelly; Prince, Brad; Watson, Hugh J. (John Wiley & Sons, 2017)
Each chapter is comprised of tightly coupled concepts and section-level student activities that transport your students from passively learning about IS to doing IS in a realistic context. The integration of Microsoft Excel and Access exercises at the end of every chapter enables students to practice their Microsoft application skills in the context of the chapter material. ThroughWileyPLUS, each small section of concept and the accompanying activities can be assigned separately, which provides a uniquely flexible offering for instructors.